209k views
0 votes
Y=-4/3x+6; y=2
I need that to be done in subsitution or elimination

User Rifaj
by
5.0k points

2 Answers

3 votes

Rewrite equations:

y=2;y=

−4

3

x+6

Step: Solvey=2for y:

y=2

Step: Substitute2foryiny=

−4

3

x+6:

y=

−4

3

x+6

2=

−4

3

x+6

2+

4

3

x=

−4

3

x+6+

4

3

x(Add 4/3x to both sides)

4

3

x+2=6

4

3

x+2+−2=6+−2(Add -2 to both sides)

4

3

x=4

4

3

x

4

3

=

4

4

3

(Divide both sides by 4/3)

x=3

Answer:

x=3 and y=2

User Orphid
by
4.8k points
3 votes
For substitution it would be -4/3 (2) +6 and then you solve!
User Robbrit
by
4.4k points